Counseling, Detection of Children’s Fine Motor Development and Sensory Play Finger Intervention in Preschool Children in Bogor District - Silawati, Vivi; Putri Azzahroh; Badria Laili (International Journal of Community Services, 2024)
According to the Central Statistics Agency (2018), to maximize the development potential of children aged 0-6 years, the government has created an early childhood education (PAUD) program. The PAUD program prioritizes children's physical growth and development (fine and gross motor coordination) and children's intelligence, socio-emotional skills, and language and communication, which aim to provide positive stimulation for children's growth and development. Stimulation for children needs to be done as early as possible. Its implementation can be carried out regularly as a prevention because when stimulation is carried out, the hormones needed for children's development can be produced by the body. One of them is by doing sensory play activities. Sensory play is a game that can train children to use one or more senses. Sensory play becomes a stimulus that will enter the child's brain, which then the nervous system will process it by producing a sensation that can encourage the child's senses to move, this is called a stimulus-response. When children get a lot of stimulus, children will get more and more pleasant experiences (Munzilin, et al., 2021). The methods used are lectures and discussions. The implementation of community service was carried out at PAUD Uswatun Hasanah, Bogor Regency on January 8, 2024, with 38 participants. After the community service activity, participants learned the importance of providing stimulation for children's fine motor development.